Online Profitability Exposure, Firm Value, Along With Monitoring Of The Environment - Frasetyo Angga Saputra; Dwi Prastowo Darminto; Syaril Djaddang (Publikasi Indonesia, 2024)
The overall market value of all the issued shares of the firm is its enterprise value. Incredibly, one amount of financiers have the cash for reimbursement to purchase all or a portion of the firm, and it is based on a book worth to a business's assets and liabilities. Enterprise worth may be calculated using a variety of methods, and the approach you use will often count on the particulars of your business and the assessment's goal. With sustainability reporting serving as a mediator factor, Its goal aims to ascertain how Internet financial performance and sustainability reporting impact corporate value. 33 businesses operating in the mining and industrial sectors between 2020 and 2022 make up the study's sample. The financial and sustainability reports of such firms provided the data for our investigation. The results demonstrate sustainability regarding monetary results in terms of the Internet.